Auditor's guide to IT auditing - Cascarino, Richard; Cascarino, Richard (Hoboken, N.J. : Wiley, 2012)
'Step-by-step guide to successful implementation and control of IT systems--including the CloudMany auditors are unfamiliar with the techniques they need to know to efficiently and effectively determine whether information systems are adequately protected. Now in a Second Edition, Auditor's Guide to IT Auditing presents an easy, practical guide for auditors that can be applied to all computing environments. Follows the approach used by the Information System Audit and Control Association's model curriculum, making this book a practical approach to IS auditing Serves as an excellent study guide for those preparing for the CISA and CISM exams Includes discussion of risk evaluation methodologies, new regulations, SOX, privacy, banking, IT governance, CobiT, outsourcing, network management, and the Cloud As networks and enterprise resource planning systems bring resources together, and as increasing privacy violations threaten more organization, information systems integrity becomes more important than ever. Auditor's Guide to IT Auditing, Second Edition empowers auditors to effectively gauge the adequacy and effectiveness of information systems controls'--
Rev. ed. of: Auditor's guide to information systems auditing.
Includes index.
Keywords: Electronic data processing -- Auditing; BUSINESS & ECONOMICS / Auditing